English Language Teacher's Roles as Viewed by EFL Students - Resna Suci Nurfalah; Emmas Pupah (English Learning Innovation (englie), 2022)
The teaching profession is complex and multifaceted. Beyond simply educating, teachers have many critical roles in the classroom. Recent research on teachers' roles has revealed crucial roles that differ by educational level. However, little is known about EFL students' perceptions of the functions of English language teachers, particularly at primary and secondary education levels. To fill the gap, this descriptive qualitative research reflects on EFL students' perception of English teachers' role in the classroom. The questionnaire, followed by a semi-structured interview to examine the data in more detail, was given to the first-grade junior high school students. After analyzing the data by using mixed-method, it was determined that students viewed the teachers' position as the resource to be the most important and the teachers' role as the organizer to be the least important. This result means that in most classroom activities, the students still depend on their teacher and see the teacher as the center of the class. This research can serve as a reflection for teachers to switch roles as organizers rather than be the students' sources. Hence the students can independently be responsible for their learning with teachers' support. Further research is recommended to investigate the teachers' role from students' and teachers' perspectives.